2019
DOI: 10.1093/icvts/ivz079
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of experience in lung cancer screening in Gdańsk, Poland: a comparative study of the evaluation and surgical treatment of 14 200 participants of 2 lung cancer screening programmes

Abstract: OBJECTIVES The European Society of Thoracic Surgeons’ recommendations confirm the implementation of lung cancer screening in Europe. We compared 2 screening programmes, the Pilot Pomeranian Lung Cancer Screening Programme (pilot study) and the Moltest Bis programme, completed in a single centre. METHODS A total of 8649 healthy volunteers (aged 50–75 years, smoking history ≥20 pack-years) were enrolled in a pilot study between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…[28][29][30][31] The rate of early lung cancer cases diagnosed during the first round of screening in our cohort (1.34%, 7 cancers per 523 patients) was similar to that reported by other Polish screening university centers: 1.24% in Gdańsk and 0.7% in Szczecin. 43,44 Clinical studies have shown that emphysema with or without COPD is a significant risk factor of lung cancer, even in nonsmokers (hazard ratio, 1.66; 95% CI, 1.06-2.59). 45,46 The predictive value of COPD in lung cancer (high -risk group according to NCCN v. 2.2019) 14 is high enough to consider lower pack -year thresholds for screening eligibility.…”
Section: Referencesmentioning
confidence: 99%
“…[28][29][30][31] The rate of early lung cancer cases diagnosed during the first round of screening in our cohort (1.34%, 7 cancers per 523 patients) was similar to that reported by other Polish screening university centers: 1.24% in Gdańsk and 0.7% in Szczecin. 43,44 Clinical studies have shown that emphysema with or without COPD is a significant risk factor of lung cancer, even in nonsmokers (hazard ratio, 1.66; 95% CI, 1.06-2.59). 45,46 The predictive value of COPD in lung cancer (high -risk group according to NCCN v. 2.2019) 14 is high enough to consider lower pack -year thresholds for screening eligibility.…”
Section: Referencesmentioning
confidence: 99%
“…This study assessed the performance of these three risk prediction models in a large lung cancer screening cohort from Gdańsk, Poland. Throughout last ten years over 15,250 individuals have been screened in two lung cancer screening programmes in one screening centre (11,12). This retrospective study was based on full data collected during the latest screening programme conducted in Gdańsk-the MOLTEST BIS programme.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed methodology of the screening management in the MOLTEST BIS programme was the subject of the previous publication (11). Primarily, the MOLTEST BIS programme was a validation study for the early lung cancer biomarkers, which were discovered in our previous lung cancer screening programme (12).…”
Section: Moltest Bis Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Stage I was diagnosed in 64% to 70% of detected cancers. 5 The results of these studies contributed to the awareness of the risk of lung cancer in society and established a knowledge-base on the low-dose CT for early lung cancer detection. The final results of the National Lung Screening Trial 6 and NELSON trial 7 prompted the development of the first Polish large-scale lung cancer early detection program.…”
Section: Lung Cancer Screeningmentioning
confidence: 99%